2023
DOI: 10.3390/nu15234934
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Micronutrient Intake and Its Relationship with the Malnutrition–Inflammation–Frailty Complex in Patients Undergoing Peritoneal Dialysis

Gordon Chun-Kau Chan,
Jack Kit-Chung Ng,
Phyllis Mei-Shan Cheng
et al.

Abstract: Background: The relationship between dietary patterns and the malnutrition–inflammation–frailty complex in patients undergoing peritoneal dialysis (PD) is currently unknown. Our objective was to measure dietary nutrient intake and evaluate its association with malnutrition, inflammation, and frailty. Methods: We prospectively recruited adult PD patients. We assessed their dietary nutrient intake using a food frequency questionnaire. Frailty, malnutrition, and inflammation were evaluated by validated Frailty Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…From the limited evidence available on the diets of people undertaking PD, adherence to the renal diet prescription is estimated to range from 38% to 65.8% [5]. Dietary energy has been reported as inadequate in several small cross-sectional studies [6][7][8][9][10] and adequate in one [11]. Similarly, protein intake is often reported as inadequate [6,[8][9][10]12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the limited evidence available on the diets of people undertaking PD, adherence to the renal diet prescription is estimated to range from 38% to 65.8% [5]. Dietary energy has been reported as inadequate in several small cross-sectional studies [6][7][8][9][10] and adequate in one [11]. Similarly, protein intake is often reported as inadequate [6,[8][9][10]12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary energy has been reported as inadequate in several small cross-sectional studies [6][7][8][9][10] and adequate in one [11]. Similarly, protein intake is often reported as inadequate [6,[8][9][10]12,13]. From two studies that reported food group intake [9,14], data were incomplete and reported some, but not all, core food groups.…”
Section: Introductionmentioning
confidence: 99%